PENGARUH BRAND PERFORMANCE DAN VALUE PRICING TERHADAP REPEAT PURCHASE PRODUK SMARTPHONE XIAOMI DI JAKARTA - Indra Indra Kurniawan; Lily Harjati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2020)
The diversity of smartphones causes market competition to grow and develop. The level of competition that has led to the emergence of various brands and prices so that marketers are required to be able to carry the product being sold and can influence a customer who will buy the product. Then bring the company to innovate in terms of promotion, create new products or develop existing products and be able to increase the value of its brand. Xiaomi company is one of the pioneers in the development of smartphones today. The purpose of this study is to determine the Brand Performance and Value Pricing has an influence on the Repeat Purchase of Xiaomi smartphone products in Jakarta. Theories used in this research are Brand Performance, Value Pricing and Repeat Purchase. The independent variables in this study are Brand Performance and Value Pricing, while the Dependent Variables in this study are Repeat Purchases. The object of this research is the Xiaomi Smartphone. Data analysis techniques used in this study are Descriptive Analysis, Validity Test, Reliability Test, Classical Assumption Test and Multiple Regression Analysis. Sampling is done by non-probability sampling using the judgment sampling method. The classical assumption test analysis results state that the regression model meets the assumption requirements that are normally distributed, do not contain heteroscedasticity, do not occur multicollinearity and autocorrelation does not occur. The results of multiple regression analysis show that the regression model can predict repeat purchases and based on the t test illustrates that the value of sig. under 0.05 so that it can be concluded that brand performance and value pricing variables have significance so that the hypothesis can be accepted. The conclusion in this study is that Brand Performance and Value Pricing have a positive effect on Repeat Purchase of Xiaomi Smartphone Products in Jakarta. Keywords: Brand Performance, Value Pricing, Repeat Purchase